Modelling Friction Phenomena in the Dynamics Analysis of Forest Cranes - URBAŚ, Andrzej; SZCZOTKA, Marek (Engineering Transactions, 2016)
A dynamics analysis of a forest crane, with a special consideration of friction in joints, is considered. The LuGre friction model is applied in all revolute and prismatic joints of the crane. A load handling simulation is performed for a typical operation. Various friction factors and loading conditions are examined. As shown, friction phenomena plays a significant role when defining loads acting on crane elements.